Impact of Hurricane Irene and Tropical Storm Lee on riparian zone hydrology and biogeochemistry. Issue 2 (14th November 2016) - Vidon, Philippe; Marchese, Sara; Rook, Stephen
Abstract: Although riparian zones are well known to reduce nitrogen (N) and phosphorus (P) runoff to streams, they also have the potential to affect greenhouse gas (CO2, N2 O, and CH4 ) fluxes to the atmosphere. Following large storms, soil biogeochemical conditions often become more reduced, especially in oxbow depressions and side channels, which can lead to hot moments of greenhouse gas production. Here, we investigate the impact of the remnants of Hurricane Irene and Tropical Storm Lee on riparian zone hydrology (water table: WT), and biogeochemistry (oxidation‐reduction potential [ORP], dissolved oxygen [DO], NO3 −, PO4 3 −, CO2, N2 O, CH4 ). Results indicate that large storms have the potential to reset WT levels for weeks to months. Overbank flooding at our site following Irene and Lee led to the infiltration of well‐oxygenated water at depth (higher DO and ORP) while promoting the development of anoxic conditions within soil aggregates near the soil surface (increased N2 O and CH4 fluxes). A short‐term increase in CO2 emission was observed following Irene at our site where aerobic respiration was water‐limited. Over a 2‐year period, an oxbow depression exhibited higher WT, higher N2 O and CH4 fluxes (hot moment), higher CO2 fluxes (seasonal), and lower NO3 − concentrations (seasonal) than the rest of the riparian zone. However, neither Irene, nor Lee, nor the oxbow depression significantly impacted PO4 3 − . Dissolved organic carbon, ORP, and DO data illustrate the time‐lag (>20 years) between the creation of an oxbow depression and the development of reducing conditions despite clear differences in riparian zone and oxbow WT dynamics.